Sequence analysis of thegene encoding polyhedrin of monodon baculovirus (MBV) infected in penaeid shrimp (Penaeus monodon) in Vietnam - An, Nguyễn Thị Giang; Quyền, Đồng Văn; Kháng, Đinh Duy (Vietnam Journal of Biotechnology, 2018)
Monodon Baculovirus (MBV) is a causative agent in farmed shrimp. It is a double-stranded DNA virus with genome size of 119.638 bp. MBV virions are free in the nuclei or covered by the occlusion bodies(Obs) constructed by polyhedrin matrix proteins of MBV. OBs serve to protect the occluded virions from the outside environment for extended periods until they are ingested by insect larvae. Polyhedrin is a type of protein covering the viruswith size from 17 to 23 nm, as well as a surface antigen used for Baculovirus detection. Sequence analysis of the gene coding for polyhedrin (polhed) showed that their open reading frame (ORF) was 1,371 bp long and coding for a polypeptide of 457 amino acids.The alignment of nucleotide sequencesof all polyhedrin genes including those of MBV isolated in Vietnam and from GenBank showed that polhed from Vietnam has 97%, 97% and 94% sequence identity compared to that of Thailand, Taiwan and India, respectively. Amino acid analysis revealed that the insertions occur at the sites 72-73 with 4 aa (p.72_73insNEPM) and at 81-82 with 7 aa (p.81_82ins PYHNSPN) in the MBV isolated in Vietnam in comparison with that of Thailand. In addition, we also observed other amino acid substitutions in the protein sequence as: p.Thr55Gly, p.Glu63Asp, p.Asn72Asp, p.Glu92Gly, p.Met93Leu, p.Lys108Asnand p.Lys113Asn. These amino acid changes may affect the protein structure and reduce the specificity of the antigen. Therefore, the foreign kits for MBV diagnosis may have less specificity when using for inland MBV strains detection. The result of our research suggests that MBV which cause diseases in Vietnamese shrimps have notable genetic deviation compared to that of Thailand’s and other countries’ in the world